THE EFFECTIVENESS OF RELAXATION TECHNIQUES IN REDUCING ANXIETY AT KRETEK BANTUL PUBLIC HEALTH CENTER: EFEKTIFITAS TEKNIK RELAKSASI DALAM MENURUNKAN KECEMASAN DI PUSKESMAS KRETEK BANTUL - Furqan Nugraha Rahman; Elli Nur Hayati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
This study aims to test relaxation techniques to lower anxiety in Prolanis members. Participants in this study numbered eight people who obtained anxiety scores in the moderate and severe categories. Design research using Pre-experimental One group pretest-postest design. The instrument used is the Beck Anxiety Inventory (BAI) anxiety scale. Treatment it men gave is a relaxation technique consisting of eight sessions conducted approximately for three weeks. The results of quantitative analysis using Wilcoxon nonparametric statistics showed significant differences between before and during the activity with Z=-2,207 with a value of p=0.027 (p<0.05, significant). Qualitative analysis is conducted by analyzing observations, interviews, and worksheets as supporters. The results showed that relaxation technique training was shown to lower anxiety levels in each participant.